Специфичность некоторых ферментных систем кишечника хищных клещей Phytoseiulus persimilis и Amblyseius longispinosus - Барабанова, В.В. (Вестник зоологии, 1985)
Some common and different features in the intestinal enzymatic system functions were found in two species under study. Carbohydrases in both species have the same hydrogen-ion concentration optima that coincide with pH optima of similar enzymes of the prey and are close to the intestinal pH value. Absolute glucosidase activity values and relation of amylase activity to substrate concentration are parallel in both. Maximal speed of enzymatic reactions and optimal substrate concentrations of glucosidase and peptidase are slightly different: pH optima of all the studied enzymes differ by 0.5, enzyme activity range-by 1.0 pH. The species considerably differ in absolute values of amylase and protease activity, which is associated with different carbohydrases ratio in enzymatic spectrum and, thus, in different Km values.